Strategic Impression Management of a Music Celebrity: A Narrative-Visual Analysis of the Documentary Film "All Access to Rossa 25 Shining Years" - Rizki Ramadhan Hidayat; Indra Novianto Adibayu Pamungkas (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: During this time, I had fit into their narrative as a child and teenager through social media, music, movies, video games, and navigated an ever-evolving field of entertainment that has improved and still fostered emotional connection. In addition, documentary films are an increasingly important avenue for self-representation; however, research examining these works among Indonesian music celebrities is still in its infancy. Objective: This study explores Rossa's intended multi-layered self-presentation strategies in the 2024 documentary All Access to Rossa 25 Shining Years and how audiences from different generations experience them. Methods: A qualitative descriptive design with narrative-visual analysis was used. We conducted thematic analysis (NVivo) of 20 semi-structured audience interviews using an approach based on the Miles et al.  interactive model. Results: Six themes were identified: Front Stage, Back Stage, Impression Strategy, Impression Motivation, Media Construction, and Audience Impact. The authors coined the term "Transcendent Persona Architecture," which is based on authenticity, vulnerability, and integrity. Conclusion: The documentary served as a branding device. Image credibility, emotional integrity, and authenticity could challenge the conventional representation of celebrity images in Indonesian music.